Spatial expression of claudin 18.2 in matched primaries and metastases of tubo-ovarian carcinoma of all subtypes - Wagner, Paul; Gaß, Paul; Pöschke, Patrik; Eckstein, Markus; Gloßner, Laura; Hartmann, Arndt; Beckmann, Matthias; Fasching, Peter; Rübner, Matthias; Emons, Julius; Erber, Ramona (Virchows Archiv, 2024)
Physiologically, claudin 18 splice variant 2 (CLDN18.2) expression is restricted to the gastric epithelium, but its expression has been detected in solid cancers. Zolbetuximab, a chimeric IgG1 antibody targeting CLDN18.2, has demonstrated promising effects in patients suffering from CLDN18.2-positive, HER2-negative locally advanced gastric cancer and is currently being studied further. To date, little is known about CLDN18.2 expression in other histological subtypes of tubo-ovarian carcinoma (TOC) and their matching metastases. Using a cohort of all histological TOC subtypes, we investigated the immunohistochemical (IHC) CLDN18.2 expression in both TOCs (n = 536), their matching metastatic tissue (n = 385) and in 93 metastases without primary. Tissue microarrays comprised both the tumor center and periphery. IHC positivity was defined as biomarker expression of ≥ 75% in tumor cells with moderate-to-strong membranous staining. Overall CLDN18.2 positivity was 4.1% (21/515) in the TOC centers and 3.6% (18/498) in their peripheries. In primaries of mucinous tubo-ovarian carcinoma (MTOC), CLDN18.2 positivity rates were 45% (18/40) and 36.6% (15/41), respectively. Positivity rates for the corresponding metastases were 33% (4/12, center) and 27% (3/11, periphery). The expression was relatively homogenous throughout all tumor sites. With no expression in 99.5% of nonmucinous tumors, CLDN18.2 positivity was almost exclusively seen in the mucinous subtype. In tubo-ovarian carcinoma, CLDN18.2 expression was, with rare exceptions, restricted to the mucinous subtype. Among them, 33% of metastasized MTOCs presented with CLDN18.2 positivity. Hence, CLDN18.2 might display a promising target for personalized therapy in patients with advanced MTOC.
CRIS-Team Scopus Importer:2024-02-16
Keywords: CLDN18.2; Immunohistochemistry; Mucinous tubo-ovarian carcinoma; Targeted therapy; Tubo-ovarian cancer